2023
DOI: 10.1213/ane.0000000000006436
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of NAc D1R-VP/LH Circuits Promotes Reanimation From Sevoflurane Anesthesia in Mice

Abstract: BACKGROUND: Emerging evidence has uncovered a vital role of nucleus accumbens (NAc) neurons that express the dopamine D1 receptor (D1R) and its upstream neural circuit in general anesthesia (GA) regulation. However, the underlying downstream neural basis of the modulation of GA emergence by NAc D1R neurons remains unknown. In the present study, we explored the downstream neural mechanism of NAc D1R neurons in the modulation of emergence from sevoflurane GA. METHODS: We traced the axonal projections of NAc D1R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Research has indicated that EEG delta (0.5-4 Hz) power gradually increases from the state of awakening to anesthesia [20]. The results showed a significant reduction in the time to ROC in the caspase-3-mediated ablation group of mice, from 690 (72) s to 520 (48) s (p = 0.02) (Figure 3A,B,D). This was accompanied by a decrease in the proportion of delta waves during the emergence period, from 29.2 (1.5) % to 24.0 (1.1) % (p = 0.039) (Figure 3A,B,E,F).…”
Section: Ablation Of Lhb Neurons Facilitates the Emergence Of Ciprofo...mentioning
confidence: 91%
See 1 more Smart Citation
“…Research has indicated that EEG delta (0.5-4 Hz) power gradually increases from the state of awakening to anesthesia [20]. The results showed a significant reduction in the time to ROC in the caspase-3-mediated ablation group of mice, from 690 (72) s to 520 (48) s (p = 0.02) (Figure 3A,B,D). This was accompanied by a decrease in the proportion of delta waves during the emergence period, from 29.2 (1.5) % to 24.0 (1.1) % (p = 0.039) (Figure 3A,B,E,F).…”
Section: Ablation Of Lhb Neurons Facilitates the Emergence Of Ciprofo...mentioning
confidence: 91%
“…Immunofluorescence was performed as described previously [ 20 , 48 ]. The mice were deeply anesthetized with pentobarbital sodium and intracardially perfused with phosphate-buffered saline (PBS), followed by 4% paraformaldehyde (PFA) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, EEG spectral analysis showed that optogenetic inhibition induced an increase in beta waves during the induction period, and a significantly increased delta waves and a decreased alpha, beta and gamma waves during the emergence period ( Zhang J. et al, 2023 ). Bao et al also found that optogenetic activation of the terminals of the nucleus accumbens dopamine D1 receptor-expressing neurons in the ventral pallidum induced cortical activation and behavioral emergence ( Bao et al, 2023 ).…”
Section: Basal Forebrainmentioning
confidence: 99%
“…Under deep anesthesia, optogenetic activation of these neurons changed the EEG pattern from the burst suppression to a relatively active state with low amplitude and high frequency waves. In addition, the BSR of ChR2 mice decreased significantly during optical stimulation ( Bao et al, 2023 ). Overall, these results suggest that the nucleus accumbens dopamine D1 receptor-expressing neurons has a modulatory effect on the induction and emergence processes of sevoflurane anesthesia.…”
Section: Basal Forebrainmentioning
confidence: 99%
“…In a study by Oishi et al (2017) optogenetic activation of NAc neuronal terminals within the VP was found to decrease the firing rate of VP neurons and induce inhibitory postsynaptic currents, a phenomenon not observed in other downstream nuclei of the NAc. Furthermore, Bao et al (2023) reported that the activation of the NAc D1 R -VP pathway could facilitate the recovery of mice from sevoflurane anesthesia. These studies collectively demonstrate the close relationship between the NAc and VP, as well as their ability to regulate the process of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%